Student nurses digital literacy levels: Lessons for curricula - Brown, Janie; Morgan, Alani; Mason, Jaci; Pope, Nicole; Bosco, Anna (Wolters Kluwer Health, 2020)
The rapid uptake of technology is changing the way health professionals provide care to patients and communities. While this presents opportunities to improve, enhance, and positively transform care and treatment, graduates must have the requisite knowledge, skills, and attitudes to make effective use of the technology and data available to them. This research explored nursing students' self-reported digital literacy levels. We undertook a student survey at one university in Australia, utilizing the validated Self-Assessment Nursing Informatics Competencies Scale-SF30 instrument. Overall, 90% of students rated their basic computer knowledge and skills as at least "competent" including performing basic troubleshooting, using the Internet, and conducting online literature searches. However, only 55% of students considered their overall applied computer skills as at least "competent," which included using applications for diagnostic coding and to extract data from clinical data sets. Students have digital literacy in everyday settings; however, their ability to translate this into practice is limited, restricting their access to and use of digital tools in the workplace. Our findings provide the opportunity to address practice issues related to digital literacy and to embed appropriate content in curricula to enable the delivery of improved patient care and the appropriate use of data in various settings.